Focusing attention on circular pedaling reduces movement economy in cycling - Schücker, L.; Fleddermann, M.; de Lussanet, M.; Elischer, J.; Böhmer, C.; Zentgraf, K. (Psychology of Sport and Exercise, 2016)
Abstract: Previous research has shown that focus of attention affects movement economy in endurance tasks. This experimental study was designed to take a closer look at how focusing attention on special characteristics of endurance cycling actions can influence metabolic energy costs. Twenty-five trained cyclists completed 4x6min time trials at submaximal intensity on a cycling ergometer. For each of the four time trials, they were instructed to adopt a different focus of attention: (1) circular pedaling, (2) force production of quad muscles, (3) head position, (4) stimuli in a cycling video. The order of conditions was counterbalanced. The main dependent measure was movement economy (i.e., oxygen consumption at a given workload). The results show that a focus on the circular pedaling action leads to reduced economy than a focus on the video (p=0.001). Focusing on smooth and circular pedaling includes a continuous monitoring of the cycling action, which could disturb the rhythmical nature of movement execution, thereby leading to detriments in movement economy.